2015
DOI: 10.1111/ajt.12968
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR and -DQ Eplet Mismatches and Transplant Glomerulopathy: A Nested Case–Control Study

Abstract: We conducted a nested case-control study from a cohort of adult kidney transplant recipients to assess the risk of transplant glomerulopathy (TG) as a function of donor and recipient HLA-DR and -DQ incompatibility at the eplet level. Cases (n ¼ 52) were defined as patients diagnosed with transplant glomerulopathy based on biopsies showing glomerular basement membrane duplication without immune complex deposition. Controls (n ¼ 104) with a similar follow-up from transplantation were randomly selected from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 87 publications
(118 reference statements)
4
88
1
Order By: Relevance
“…Interestingly, the occurrence of clinical rejection episodes was identified as an independent predictor of dn DSA development (odds ratio, 2.6 per rejection episode, P < 0.001). In a separate study of 1753 kidney transplant recipients followed for 3.97 ± 2.71 years, Sapir-Pichhadze et al 17 showed an association between class II HLA eplet mismatches and the development of transplant glomerulopathy. 17 Compared to less than 27 class II (HLA-DR + DQ) eplet mismatches, 27 to 43 eplet mismatches were associated with a greater than twofold risk of transplant glomerulopathy (odds ratio, 2.84; P = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the occurrence of clinical rejection episodes was identified as an independent predictor of dn DSA development (odds ratio, 2.6 per rejection episode, P < 0.001). In a separate study of 1753 kidney transplant recipients followed for 3.97 ± 2.71 years, Sapir-Pichhadze et al 17 showed an association between class II HLA eplet mismatches and the development of transplant glomerulopathy. 17 Compared to less than 27 class II (HLA-DR + DQ) eplet mismatches, 27 to 43 eplet mismatches were associated with a greater than twofold risk of transplant glomerulopathy (odds ratio, 2.84; P = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…Although HLA-DQ and -DR may be closely related at an antigen level, it has been shown that small differences in one or more epitopes between donors and recipients at either locus are sufficient to generate a humoral and/or T cell-mediated immune response (18,19). In a nested casecontrol study of a cohort of 52 kidney transplant recipients with established transplant glomerulopathy, an increasing number of HLA-DQ and HLA-DR eplet mismatches was associated with an increased risk of developing transplant glomerulopathy, suggesting that epitope mismatches at either HLA-DQ or HLA-DR locus are equally important in predicting graft outcomes (5). Future studies evaluating both broad antigen and epitope HLA-DQ mismatches are crucial in establishing a better understanding of the association between HLA-DQ mismatches and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although differences in HLA-DQ matching between donors and recipients have been shown to be associated with adverse graft outcomes, matching at the HLA-DQ locus is not explicitly considered in the allocation algorithm for deceased donor kidney transplantation (4,5). There is a general consensus suggesting that HLA-DQ mismatches are unlikely to have a major effect on graft survival, because serologic compatibility for HLA-DR usually ensures a corresponding compatibility for HLA-DQ (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that, in the context of therapeutic and diagnostic advances, the effect of RMM on graft loss would be attenuated compared with historical cohorts. We further hypothesized that the effect of RMM may be greater for class 2 RMM (given increasing evidence of the deleterious effect of class 2 mismatch on transplant outcomes) [9][10][11] and modified by predefined panel-reactive antibody (PRA), immunosuppression, and nephrectomy of the first transplant. Exploratory analyses for interactions between RMM and these covariates were also performed.…”
mentioning
confidence: 99%